Pengembangan Multimedia Pembelajaran Interaktif pada Materi Fungsi Organ Tubuh Manusia Kelas V SD - Fardani, Findi; Afriyaningsih, Yunika; Suriyana, Suriyana (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2025)
This study aims to develop an Interactive Learning Multimedia on the topic of human organ functions for fifth-grade elementary students to ensure its feasibility for both learners and teachers. The lack of variation in teaching methods has limited students’ learning potential. Therefore, the researcher developed interactive multimedia learning materials for Science subjects, specifically on human organ functions. The development model used is ADDIE (Analysis, Design, Development, Implementation, Evaluation), but this research is limited to the Development stage due to time constraints and focus on product creation rather than implementation or evaluation. This stage includes product creation, validation, and testing. Validation was conducted by three experts: a language expert, a media expert, and a material expert. The trial was limited to validation to determine product feasibility. The media was designed using Canva for visual design, Quizizz for interactive quizzes, and Google for relevant images and animations. It is expected that this Interactive Learning Multimedia will enhance students’ motivation and understanding of human organ functions and contribute to improving the quality of Science learning in elementary schools